(5E,7E)-4,5,6 Trihydroxy-3-(hydroxymethyl)tetrahydro-2H-pyran-2-ylheptadeca-5,7-dienoate from Euclea crispa (L.) Inhibits Ovarian Cancer Cell Growth by Controlling Apoptotic and Metastatic Signaling Mechanisms - Chella Perumal Palanisamy; Bo Cui; Hongxia Zhang; Selvaraj Jayaraman; Ponnulakshmi Rajagopal; Vishnu Priya Veeraraghavan (Bioinorganic Chemistry and Applications)
Bioactive compound (5E,7E)-4,5,6 trihydroxy-3-(hydroxymethyl)tetrahydro-2H-pyran-2-ylheptadeca-5,7-dienoate (compound 2) was isolated from Euclea crispa (E. crispa) by the chromatographic methods. Further, the compound was confirmed by spectroscopic techniques such as ultraviolet-visible (UV/Vis) spectrometer, Fourier transform infrared (FTIR) spectrometer, and 1H and 13C nuclear magnetic resonance (NMR). Compound 2 exhibited a significant antioxidant activity with IC50 values. It restrained the auxesis of HO-8910 cells in a shot-dependent mode. CXCR4, HER2, and Akt proteins involved in cell proliferation and metastasis were found to be significantly reduced (p<0.05). The protein that is responsible for the death of cells (Bcl-2 and Bcl-xL) was reduced (p<0.05), while the protein expression of p53 and caspase-9 was increased (p<0.05) in compound 2-treated HO-8910 cells. The results of molecular docking analysis showed the binding affinity with CXCR4 and HER2. Thus, compound 2 can serve as a promising chemotherapeutic agent for the intervention of ovarian cancer. The findings of this study conclude that compound 2 from E. crispa might work as a potential antioxidative and chemotherapeutic agent. The in vivo studies and attempts will pave way for this compound to be an effective drug hereafter.